Diversity in unconventional protein secretion - Rabouille, Catherine; Malhotra, Vivek; Nickel, Walter (Journal of cell science, 2012)
Eukaryotic cells use the endoplasmic reticulum (ER)-to-Golgi membrane pathway for the secretion of the vast majority of secretory proteins. This process is initiated by signal-peptide-dependent protein translocation into the lumen of the ER followed by vesicular transport of secretory cargo to the